General framework for automated manufacturing systems: multiple hoists scheduling solution - Aguirre, Alejo (2013)
This work presents a generic MILP-based framework for the scheduling of Hoist transportation devices in a complex Automated Manufacturing System. The main contribution of this approach relies on the possibility to tackle multiple hoists in a multiproduct multistage batch process under different production schemes considering: heterogeneous production recipes, multiple units per production stage, possible recycle flows, sequence-dependent transfers and flexible processing times. The effectiveness of this approach was tested in a real industrial application example which was solved with acceptable computational effort.